Heme drives hemolysis-induced susceptibility to infection via disruption of phagocyte functions. - Martins, R; Maier, J; Gorki, A; Huber, K; Sharif, O; Starkl, P; Saluzzo, S; Quattrone, F; Gawish, R; Lakovits, K; Aichinger, M; Radic-Sarikas, B; et al. (Nature Publishing Group, 2016)
Hemolysis drives susceptibility to bacterial infections and predicts poor outcome from sepsis. These detrimental effects are commonly considered a consequence of heme-iron serving as a nutrient for bacteria. Here, we employed a Gram-negative sepsis model and found that elevated heme levels impaired the control of bacterial proliferation independent of heme-iron acquisition by pathogens. We demonstrate that heme strongly inhibited phagocytosis and migration of human and mouse phagocytes by disrupting actincytoskeletal dynamics via DOCK8-triggered Cdc42 activation. A chemical screening approach revealed that quinine effectively prevented heme effects on the cytoskeleton, restored phagocytosis and improved survival in sepsis. These mechanistic insights provide potential therapeutic targets for patients with sepsis or hemolytic disorders.